Experimental Observations and Statistical Modeling of Crack Propagation Dynamics in Limestone by Acoustic Emission Analysis During Freezing and Thawing. Issue 7 (23rd July 2021) - Maji, Vikram; Murton, Julian B.
Abstract: The timing and location of microcracking events, their propagation and coalescence to form macrocracks, and their development by tension, shearing or mixed modes are little known but essential to understanding the fracture of intact rock by freezing and thawing. The aims of the present study are to investigate the mechanisms and transition of microcracking and macrocracking during repeated freeze‐thaw, and to develop a statistical model of crack propagation that assesses the distance and angular relationship of neighboring cracking events arranged in their temporal order of occurrence. Eight acoustic emission (AE) sensors mounted on a 300 mm cubic block of chalk captured the three‐dimensional locations of microcracking events in their temporal order of occurrence during 16 seasonal freeze‐thaw cycles simulating an active layer above permafrost. AE events occurred mostly during thawing periods (45%) and freeze‐to‐thaw transitions (37%) rather than during freezing periods (9%) and thaw‐to‐freeze transitions (8%), suggesting that most AE (microcrack) events were driven by the process of ice segregation rather than volumetric expansion. The outcomes of a novel statistical model of crack propagation based on two boundary conditions—inside‐out and outside‐in modes of cracking—were assessed based on Bayes' theorem by testing the hypothesis that the inside‐out mode of cracking was favored by tensional activity, whereas the outside‐in mode was supported by shearing events. In both situations, the hypothesis accounted for 54%–73% confidence level. The microcrack propagation model can distinguish reasonably between cracks formed by volumetric expansion and ice segregation. Plain Language Summary: It is well known that repeated freezing and thawing of water within some porous and fine‐grained rocks can form large cracks visible to the unaided eye. But the initiation and growth of precursor tiny cracks too small to see without a microscope remain enigmatic in terms of their timing, location, growth, and coalescence to form eventually large cracks. Thus, prediction of rock fracture by frost is difficult. Here we present results from a laboratory experiment that measured the location and timing of tiny sound (acoustic) waves within a block of limestone subject to 16 cycles of freezing and thawing. The waves indicated the occurrence of tiny cracking events. Measurement of rock temperature suggested that most cracking events resulted from water migrating through the rock toward lenses of ice rather than expansion of water freezing in place within empty spaces in rock. In addition, cracks propagating outward from the block center tended to form as the rock was being pulled apart, whereas those propagating inward tended to form by scissor‐like tearing of rock. A new statistical model of rock cracking can distinguish reasonably well between cracks formed by growing ice lenses and those formed by expansion of freezing water. Key Points: Most acoustic emissions occurred during thaw of a limestone block, consistent with microcracking events due to ice segregation Microcracks propagating outward from the block center favored tensional cracking, whereas those propagating inward favored shearing events A new microcrack propagation model distinguishes reasonably between cracks formed by volumetric expansion and ice segregation